The clinical and epideiological features of tick-borne encephalitis at the endemical region of Russia’s European part - O. N. Lyubeznova; A. L. Bondarenko (Журнал инфектологии)
The aim was to study the clinical and epidemiology of various forms of tick-borne encephalitis patients in the Kirov region.We analyzed 384 medical records of patients with tickborne encephalitis in age from 18 to 78 years. The feverish form was recorded in 195 patients (50,8%), meningeal form – in 76 (19,8%), focal form – in 113 (29,4%).Tick-borne encephalitis occurs more frequently in men (61,5%) of working age (37.5% of cases of the disease recorded in the age from 45 to 60 years). Persons older than 60 years were significantly more developed focal forms (p<0,05). Transmissible path noted in 76,3%, nutritional – 7,8%, «unspecified» – 15,9%. Statistically significant at the «unspecified» way more likely to develop focal forms than febrile (p <0,01) and meningeal form (p <0,01). It noted an acute onset of the disease with severe intoxication, inflammatory syndrome, which in focal forms was significantly more pronounced than at hectic (p <0,01) and meningeal (p<0,01). In clinical structure of focal forms of the following options allocated: polioencefalitic form – 33,6%, encephalitic form – 23,0%, poliomielitic form – 11,5%, and mixed versions: encefalitic-polioencefalitic rorm – 12,4%, polioencefaliticmielitic form – 8.0%, encefalitic-poliomielitic form – 4,4% encefalitic-polioencefalitic-mielitic form – 7,1%.In 50,4% of patients were marked by the residual effects: asthenovegetative syndrome (32.0%), glaring peripheral mono and paraparesis of up and low extremities (24,3%), cerebellum ataxia – 5,8%, drooping head syndrome (4,9%), central hemiparesis (1,0%).Thus, the tick-borne encephalitis is a disease relevant to the Kirov region. Further study of the epidemiological and clinical features of the disease will allow substantiating and developing a set of measures aimed at reducing the incidence of tick-borne encephalitis.